The Alma Mater Effect: does foreign education of political leaders influence foreign policy? - Dreher, Axel (CESifo working papers, 2016)
We study whether national leaders' foreign education influences their foreign policy, measured by voting behavior at the United Nations General Assembly (UNGA). We hypothesize that “affinity” - pre-existing or developed while studying abroad - makes leaders with foreign education more likely to vote with their host country. At the same time, such leaders need to show sufficient distance to their host country and demonstrate “allegiance” to their own one, which will reduce voting coincidence. To test this theory we make use of data on the educational background of 831 leaders and the voting affinity between the countries they govern and those in which they studied. Over the 1975-2011 period, we find that foreign-educated leaders are less likely to vote in line with their host countries but more likely to vote in line with (other) G7 countries. We identify the causal effect of “allegiance” by investigating the differential effect of foreign education on voting in pre-election years compared to other years. The difference-in-difference-like results show that G7-educated leaders vote less in line with their host countries when facing an election. Overall, both “allegiance” and “affinity” affect foreign policy